Leniency in exchange for cartel confessions - Jaspers, J.D. (European journal of criminology, 2020)
Leniency offers corporations the possibility to come clean about their involvement in cartel conduct (for example, price-fixing, bid-rigging) in exchange for immunity or reduction of financial penalties. In Europe, nearly 60 percent of detected cartels are discovered through leniency. This makes leniency the most applied detection tool for uncovering cartel conduct violations. What are the considerations in applying for leniency or refraining from doing so? How do those considerations relate to private law enforcement through civil liability regarding business cartels? These questions are discussed based on semi-structured interviews (n = 34) with cartelists, competition lawyers and in-house legal counsel to study theoretical assumptions underpinning leniency arrangements in the Netherlands. This study investigates four scenarios on the use of leniency suggested in the literature and finds empirical support for only two. Strategic use of leniency and false confessions occur in the Netherlands, but to a lesser extent than the existing literature suggests. Moreover, various disincentives, and especially the rise of private enforcement, make leniency an unattractive and uncertain option for cartelists.